SKALA KARAKTER WIRAUSAHA (SK-WIRA): KONSTRUKSI DAN VALIDASI AWAL - Husna, Aftina Nurul; Zahra, Aning Az; Haq, A Amrul (Jurnal Psikologi, 2018)
This article reports development of new scale to measure entrepreneurial characters. Entrepreneurial Characters Scale (SK-WIRA) measures personality traits indicating a person’s capacity to engage in entrepreneurial activity and can be used to study tendency and suitability to work as entrepreneur. In preliminary study, entrepreneurial character is operationalized based on concepts found in literatures: achievement motivation, innovativeness, risk taking, and autonomy. Four SK-WIRA subscales were constructed according to those dimensions. In phase 1 item selection, exploratory factor analysis and reliability analysis were applied. Initial set of SK-WIRA constituted of 40-48 items per subscale was administered to university students (N = 130). It is found that items were not clustered based on the theory, but item types (favorable-unfavorable). Therefore, it is predicted that entrepreneurial characters and non-entrepreneurial characters are probably two different constructs and need to be measured using different tools. Final compilation of SK-WIRA consists only 22 items (all is favorable items) with good internal consistency (Cronbach’s α = .863). Phase 2 construct validity test using confirmatory factor analysis (CFA) confirms that SK-WIRA consists of four correlated factors. The examination of scale internal structure shows good model fit (c2/df = 244.077/205; RMSEA = .038; CFI = .943; TLI = .936; SRMR = .069).